Experimental Research of the Effects of Different Shields on Power Frequency Magnetic Induction Mitigation - Nahman, Jovan; Salamon, Dragutin; Grbić, Maja (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
The paper describes experimental research of the effects of different shields on power frequency magnetic induction mitigation. This research was performed in order to determine those materials that may be used for magnetic induction mitigation in cases where the reference level is exceeded. Using measured results, the value of the shielding factor has been calculated for all tested shields and the most efficient shields were determined.